EFFECTIVENESS OF TRANSCUTANEOUS BILIRUBIN (TCBR) MEASUREMENT IN HIGH RISK NEONATES AND TO EVALUATE THE VALIDITY OF TRANSCUTANEOUS BILIRUBIN (TCBR) WITH TOTAL SERUM BILIRUBIN (TSBR) LEVELS IN BOTH LOW AND HIGH RISK NEONATES AT A TERTIARY CARE CENTER OF.... - Shahwar, Durre; Ariff, Sabina; Tariq, Batha; Rizvi, Arjumand; Rehan, Syed; Hussain, Ali Shabbir (Pakistan Armed Forces Medical Journal, 2021)
Objective: To evaluate the utility of a Transcutaneous Bilirubin nomogram in high risk neonates and to evaluate the validity of Transcutaneous Bilirubin and Total serum bilirubin in both low and high-risk neonates. Study Design: Cross-sectional study. Place and Duration of Study: Postnatal Ward, Aga Khan University Hospital, Karachi, from May to Oct 2019. Methodology: The participants will include all neonates born and admitted in the well baby nursery with jaundice. All neonates with gestational age of <35 weeks, requiring admission in Neonatal intensive care unit, and neonates with conjugated hyperbilirubinemia will be excluded. We will stratify our neonates into high and low risk population based on predefined criteria. Eighty five neonates in low risk group and 122 neonates in high risk group will be included. Results: We aim to assess the effectiveness of Transcutaneous Bilirubin nomogram in high risk neonates as an effective and non-invasive tool in the management of neonatal jaundice in high risk neonates. We will also assess the sensitivity and specificity of Transcutaneous Bilirubin and Total serum bilirubin measurements and the analysis would be performed separately for high risk and low risk neonates to evaluate the validity of Transcutaneous Bilirubin independently in both groups. Conclusion: We hope to establish a validated phototherapy guideline based on the Transcutaneous Bilirubin nomogram, as a cost effective and noninvasive tool in the management of neonatal jaundice in both high and low risk groups in Pakistan.